Pengaruh Employee Engagement dan Kepuasan Kerja terhadap Kinerja Dosen serta Penggunaan Metode ADDIE untuk Rekomendasi Perbaikan - Rafli Syahputra, Irfan; Gusvita, Rinda; Hadi, M. Zaky (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
This study aims to test and analyze the effect of employee engagement and job satisfaction on the performance produced by lecturers of the Sumatra Institute of Technology (ITERA) and provide program recommendations to overcome performance problems that occur. The population in this study was all ITERA lecturers with a total of 574 lecturers and samples were obtained with the Slovin formula which resulted in 85 ITERA lecturers. Data collection was carried out through questionnaires and then the results were analyzed by: validity tests, reliability tests, classical assumption tests, determination coefficient tests, hypothesis tests, and multiple linear regression tests using SPSS. The method used to determine improvement recommendations is the ADDIE method. The results showed that employee engagement and job satisfaction have an influence on the performance of ITERA lecturers. Based on these results, the proposed program recommendations include the provision of benefits, socialization of IKU, and the SISTER application and training and certification designed with the ADDIE method which is expected to overcome performance problems that occur. Keywords: Employee Engagement, Job Satisfaction, Performance